John henry days eaudiobook - Whitehead, Colson (Recorded Books Inc., 2015)
J. Sutter is a bonafide junketeer—a freelance writer, travelling from city to city, hungry for free meals and the discarded sales receipts of others to claim on his expense account. Travelling into the backwoods of West Virginia to write a piece on the unveiling of the new John Henry postage stamp and the ensuing John Henry Days festival, J. continues his nearly record-setting, three-month junket binge. But when he begins to choke on a piece of prime rib at a press dinner, shadows from the past are summoned forth and he leaves the mountain a changed man. Colson Whitehead is the author of the critically acclaimed, QPB New Voices Award-winning novel, The Intuitionist. Narrated by Peter Jay Fernandez, John Henry Days is both an ingenious retelling of the American legend of John Henry and a fascinating look into the world of contemporary journalism.